Oral Maintenance Chemotherapy Using S-1/Capecitabine in Metastatic Nasopharyngeal Carcinoma Patients After Systemic Chemotherapy: A Single-Institution Experience [Corrigendum] - Guo Q; Chen M; Xu H; Lu T; Zhou H; Chen Y; Zong J; Xu Y; Chen B; Wang B; Zhu L; Pan J; et al. (Cancer Management and Research, 2020)
Guo Q, Chen M, Xu H, et al. Cancer Manag Res. 2020;12:1387–1396. The authors have advised that the explanation for the #symbol is missing in Figure 2E key on page 1392. There are also missing markers for Radiotherapy to the metastatic foci and Radiofrequency ablation in the figure. The correct figure is below.The authors apologize for these errors.   Read the original article